Development of durian peel-based adsorbent for zinc and lead ions removal - Ngabura, Mohammed (2020)
Toxic waste discharged into water bodies by anthropogenic activities is a worldwide problem. In relative to Malaysia, several reports of surface water contamination are from toxic waste discharged by manufacturing industries. For instance, the Juru and Langat rivers, Johor Straits, the marine environment of Port Klang, etc. were reportedly contaminated by toxic pollutants, including heavy metals. Similarly, discovery of several heavy metals on clam species from 34 different sites on the Malaysian coast revealed severe contamination. Ironically, Pb2+ and Zn2+ were categorically listed among the significant issues of concern in Malaysia. Therefore, the main objective of this research is to treat excess Pb2+ and Zn2+ concentrations from aqueous medium using biosorbent developed from durian waste. The basic concept is that "a waste" was applied to treat "a waste" sufficiently. Also, durian waste was transformed into a value-added biosorbent using physical, chemical, and thermal activations. The two prepared adsorbents were termed as hydrochloric acid-modified durian peel (HAMDP) and durian peel activated carbon (DPAC). Characterization of biosorbents such as particle size, SEM, BET surface area analysis, ATR-FTIR, elemental analysis, and pHPZC was performed. Subsequently, the application of adsorption studies in removing Pb2+ and Zn2+ in static (batch adsorption) and dynamic (fixed-bed column) systems was achieved. The wastewater comprises monocomponent (in a batch process) and bi-component or multi-metal ion (in fixed-bed column) systems. Real wastewater from the textile industry was also treatable using these biosorbents. The results showed that non-modified durian peel (NMDP), HAMDP, and DPAC have an average particle size of 206.7, 110.4, and 5.6 μm, respectively. BET surface area analysis revealed that NMDP, HAMDP, and DPAC have a surface area of 0.6793, 0.8807, and 9.1480 m2/g. Morphologically, the improvement of the biosorbent porosity was testified by SEM. The ATR-FTIR analysis advised the involvement of several functional groups such as hydroxyl, aliphatic, carbonyl, aromatic amines, etc. as an active site on the biosorbents that influence the adsorption mechanisms. The elemental analysis also indicated the fruitfulness of durian peels as a potential precursor for activated carbon production. Batch biosorption study revealed that the influential parameters are pH (optimum: 8.0 for Zn and 7.0 for Pb), temperature (optimum: 40 °C for Zn and 50 °C for Pb), contact time (optimum: 240 min for Zn and 60 min for Pb) with maximum adsorption capacities of 36.7 and 127.83 mg/g for Zn and Pb, respectively. Biosorbent dose of 0.5 g in 100 ml is sufficient in this study. The isotherm studies were then fitted to Langmuir and Freundlich models. Desorption and regeneration studies showed the reusability of the biosorbents. Furthermore, column studies on single and multi-metal ion systems using DPAC indicated the capability of the biosorbent in treating excess Zn and Pb in the real industrial wastewater. The process fitted to Langmuir and linear driving force (LDF) methods. Finally, real wastewater from the textile industry was tested to validate the biosorbents. The worthwhile novelty is the easiest way of an activated carbon production process suggested in this work to achieve acceptable performance of durian peels. Hence, the biosorbent applied in this research can treat heavy metals such as Zn2+ and Pb2+ in Malaysia's real industrial effluent.